PENGARUH PENAMBAHAN PUREE KULIT BUAH APEL (Malus sylvestris Mill) TERHADAP KARAKTERISTIK FRUIT LEATHER NANAS (Ananas comosus Merr) - Zahrah, Dhia Salsabila; Ina, Putu Timur; Jambe, A.A.G.N. Anom (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This research aims to identify the effect of apple peels puree consentrations on the characteristics of pineapple fruit leather and to identify the right consentration of apple peels puree to produce pineapple fruit leather with the best characteristics. This research used randomized block design with one treatment factor of the addition of apple peels with the consentrations of 5%, 10%, 15%, 20%, 25% and 30%. Each treatment was repeated 3 times, resulting in 18 experimental units. The data were then analyzed with Analysis of Variance method and if the treatment had an effect on the variable, the Duncan test were performed. The results show ed that apple peels had significant effect to crude fiber content, antioxidant activity, vitamin C, color, texture and overall acceptance of pineapple fruit leather. The addition of 30% apple peels puree consentration resulted in the best characteristic under the following criteria: 10 . 73% water content, 8 . 33% crude fiber content, 2 . 55% antioxidant activity with the IC 50 value, 3 . 03 mg AAE/g vitamin C, brown to yellow and indifferent color, texture flexible and rather liked, flavor and taste rat h er liked, and overall acceptance liked.